(untitled) (Innovative professional education, 2023)
Innovative changes in the educational process, the introduction of any innovations into the system are carried out directly by updating and changing the activity of the teacher. The effectiveness of education depends on the activity of pedagogical workers and education seekers, the availability of educational tools, organizational, scientific, methodological improvements in the educational process, the need for knowledge of members of society and other factors. Professional competence is constant work based on innovation, which is formed and improved over a long period of time. The pedagogical mastery of a teacher, an active participant in the educational process, indicates his personality, work experience, civil status, specialist status, level of mastery of pedagogical technologies, individuality of professional activity. The problem of technological support of pedagogical workers is one of the main ones for pedagogical education.